The Effectiveness of Diversion in Handling Juvenile Criminal Offenses Based on Law No. 11 of 2012 on the Juvenile Criminal Justice System and Its Implementing Regulation (Supreme Court Regulation No. 4 of 2014) - Aji Baskoro Meliala, Raden Bagus Muhammad (Institute for Law and Economics Studies, 2025)
This study aims to analyze the effectiveness of diversion implementation in handling juvenile criminal acts based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Supreme Court Regulation (PERMA) Number 4 of 2014. Diversion, which is a form of case resolution outside the court, is expected to provide legal protection to children by prioritizing a more humanistic restorative approach. This study uses an empirical legal approach with interview and documentation methods to explore primary and secondary data, focusing on selected jurisdictions within Jakarta, Bekasi, and Depok. These areas were chosen due to their varied caseloads and differing levels of diversion infrastructure. The results of the study indicate that the implementation of diversion in several regions has been running well, particularly in urban centers like South Jakarta, where coordination among institutions is more structured. However, in other areas such as Bekasi, structural and cultural challenges still hinder its effectiveness. Therefore, it is necessary to increase the capacity of law enforcement officers, as well as more intensive socialization to the community and related parties so that diversion can be implemented optimally. The new aspect of this research is the analysis of diversion practices, including those conducted at the court level. This study contributes to the development of a fairer juvenile criminal justice system that focuses on the recovery of children in conflict with the law